A living donor kidney transplant recipient with mycobacterium senegalense bacteremia: A case report. Issue 4 (11th March 2021) - Bugeja, Ann; Hae, Richard; Rajda, Ewa; Clark, Edward G.; Akbari, Ayub; Fairhead, Todd; Arianne Buchan, C.
Abstract: Mycobacterium senegalense is primarily known in sub‐Saharan Africa to cause bovine farcy, a chronic granulomatous inflammation of the skin and lymphatics in cows. Reports of M. senegalense are rare among humans. We report a unique case of M. senegalense bloodstream infection in a living donor kidney transplant recipient with multiple possible sources of infection.